Teachers’ written formative feedback on students’ critical thinking: A case study - Pedrosa-de-Jesus, Helena (2020)
This study explores innovative ways for promoting and assessing the effectiveness of teachers’ written formative feedback in the context of undergraduate studies. The investigation entails close collaboration with one Biology teacher in the context of teaching ‘evolution’. One of the particular challenges was to encourage 88 first-year biology undergraduates to produce critical analyses of a selected press release related to the topic of evolution (i.e., the advent of genetic diseases). The research approach is based on a critical social paradigm, assuming principles of actionresearch. All written documents produced by participants and semi-structured interviews (at the end of the semester) were used as part of the content analysis of data. Results show that the teacher’s written comments increased opportunities for students to search for further information, negotiate and take decisions within their group, auto- and hetero-reflect before sending their critical analyses to the teacher.